Effect of mobilization with movement on lateral knee pain due to proximal tibiofibular joint hypomobility. (3rd October 2018) - Anandkumar, Sudarshan; Miller, Jack; J. Werstine, Robert; Young, Steve
ABSTRACT: This case report describes a 45-year-old female who presented with lateral knee pain over the right proximal tibiofibular joint (PTFJ) managed unsuccessfully with rest, medications, bracing, injection, and physiotherapy. Clinical diagnosis of PTFJ hypomobility was based on concordant symptom reproduction with palpatory tenderness, accessory motion testing, and restricted anterior glide of the fibula. Intervention consisted of Mulligan's mobilization with movement and taping over the right PTFJ with immediate improvements noticed in pain, range of motion, and function. The patient was seen twice a week and was discharged after four treatment sessions. A follow-up after 6 months revealed that the patient was pain free and fully functional.